Finance, Financial Crime and Regulation: Can Generative AI (Artificial Intelligence) Help Face the Challenges? - Singh, C. (Frontiers in Law, 2025)
Generative artificial intelligence (Gen AI) has helped change the trajectory of Banking (FinTech) and Law (Reg Tech/Law Tech). Technology innovates at an astounding rate. AI and Gen AI can not only simulate human intelligence (human thinking) but also perform tasks independently. It can develop intelligence based on its experiences, process detailed and complex information whilst continually learning and re-learning to be able to undertake complex, technical, and time-consuming tasks in real time. It can identify objects, patterns, people and voices(etc.) and look for problems far earlier – this also means it can come up with solutions quickly which in critical situations is of salient importance. The economic, political, and social benefits cannot be underestimated, but must be balanced against its disruptive and destructive potential. This article explores whether Gen AI can help further revolutionise the finance industry and how it can help with risks, and the various regulatory and operational challenges faced by those firms in the United Kingdom (UK). Data is analysed alongside domestic and international published literature. The article starts by summarising current risks and challenges and then discusses how Gen AI can be embedded as part of an arsenal of tools that financial institutions can use to develop and provide solutions to regulatory and operational challenges as at January 2025.